2004
DOI: 10.1097/01.asn.0000111248.23454.19
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Defective Branching Nephrogenesis in Renal-Coloboma Syndrome by the Caspase Inhibitor, Z-VAD-fmk

Abstract: Abstract. In renal-coloboma syndrome (RCS), null mutations of the PAX2 gene cause renal hypoplasia due to a congenital deficit of nephrons; affected individuals may develop renal insufficiency in childhood. During normal kidney development, PAX2, is expressed at high levels throughout the arborizing ureteric bud (UB); recent observations suggest that one of its key roles is to suppress apoptosis in this collecting duct lineage. The authors hypothesized that increased UB cell apoptosis due to PAX2 haploinsuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…However, it is conceivable that the extent of renal parenchymal loss is modulated by the PAX2 response. We recently found that the caspase inhibitor Z-VAD-fmk can substitute for the loss of PAX2 antiapoptotic function during renal development (6). It is tempting to speculate that caspase-inhibitory drugs might ameliorate renal parenchymal loss during acute urinary tract obstruction when endogenous mechanisms are overwhelmed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is conceivable that the extent of renal parenchymal loss is modulated by the PAX2 response. We recently found that the caspase inhibitor Z-VAD-fmk can substitute for the loss of PAX2 antiapoptotic function during renal development (6). It is tempting to speculate that caspase-inhibitory drugs might ameliorate renal parenchymal loss during acute urinary tract obstruction when endogenous mechanisms are overwhelmed.…”
Section: Discussionmentioning
confidence: 99%
“…Although Pax2 appears to have a number of roles during renal development, a key function is to suppress programmed cell death in UB cells, thereby optimizing the rate of branching nephrogenesis (6,10,19,22). Heterozygous Pax2 mutant mice display increased apoptosis of UB cells without any change in proliferative rate (19,23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of increased apoptosis in Pax2 1neu mice heterozygous for PAX2 mutations may also reflect the important role of PAX2 in regulating apoptosis. In addition, increased apoptosis in homozygous congenital polycystic kidney (cpk) mice heterozygous for PAX2 mutations has been suggested to lead to the observed slowing of the progression of renal cystic disease (35,36) in mice that carry the additional PAX2 mutation compared with those without a PAX2 mutation.…”
Section: Discussionmentioning
confidence: 99%